2021
DOI: 10.1016/j.ijpx.2020.100068
|View full text |Cite
|
Sign up to set email alerts
|

A new engineering process of biodegradable polymeric solid implants for ultra-long-acting drug delivery

Abstract: We present a long-acting (LA) biodegradable polymeric solid implant (PSI) fabricated using a new process combining in-situ phase inversion and compression. This robust process allows fabrication of solid implants that can have different shapes and sizes, accommodate high drug payloads, and provide sustained drug release over several months. Herein the integrase inhibitor dolutegravir (DTG) was used to develop PSIs for HIV prevention. PSIs were fabricated using a three-step process by (a) phase inversion of DTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Notably, other groups have also modified the structure and or delivery of DTG to develop the means to extend the drug's half-life [29,[38][39][40][41]. In one LA biodegradable polymeric solid implants were developed by phase inversion producing removable implants [41].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, other groups have also modified the structure and or delivery of DTG to develop the means to extend the drug's half-life [29,[38][39][40][41]. In one LA biodegradable polymeric solid implants were developed by phase inversion producing removable implants [41].…”
Section: Discussionmentioning
confidence: 99%
“…The formulation provided sustained CAB release above established PrEP benchmarks and durable protection against SHIV infection for up to 6 months and resulted in a short drug tail upon removal [ 107 ]. Combining ISFI technology with micronization and compression, polymeric solid implants (PSI) were fabricated to provide sustained release of DTG [ 108 ] or DTG/RPV in combination [ 109 ] over several months. An injectable LA formulation of doravirine (NNRTI) that forms an implant after SC administration has also been developed and showed that drug plasma concentrations exceeded IC 95 for >5 months in mice and efficiently prevented vaginal HIV transmission after multiple HIV challenges [ 110 ].…”
Section: Approaches To Improving Existing Arvs For La Hiv Preventionmentioning
confidence: 99%
“…Some LADDS require complex manufacturing methods where organic solvents might be used which poses safety concerns. Nevertheless, LADDS have proven to be a success in improving treatment outcomes for patients suffering from chronic eye diseases, diabetes, cancer, and brain diseases; either through improving bioavailability, reducing unwanted side effects, achieving drug targeting or promoting better patient treatment adherence [230,231]. Several issues are yet to be resolved such as the cost and availability of biomaterials used to fabricate LADDS, the nature of complex systems of some LADDS, reliance of drug on external stimuli (light, laser and application of Magnetism) of the carrier for obtaining consistent drug release that make the regulatory approval of some LADDS.…”
Section: Other Applications Of 3dp Ladds In Treatment Of Chronic Dise...mentioning
confidence: 99%